2004
DOI: 10.1163/1568560043696218
|View full text |Cite
|
Sign up to set email alerts
|

Novel chemiluminescence-inducing cocktails, part II: Measurement of the anti-oxidant capacity of vitamins, thiols, body fluids, alcoholic beverages and edible oils

Abstract: Using two luminescence-inducing cocktails, two distinct patterns of inhibition of light by different anti-oxidants have been identified, comprising Group A, in which a complete inhibition of light emission which is then followed by re-emergence of light, forming apparent S-shaped curves or similar shapes. This light pattern is induced by the "classical" anti-oxidants, ascorbate, vitamin E, uric acid, thiols, deferoxamine, as well as by anti-oxidant agents present in plasma, saliva, urine and in extracts derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 9 publications
1
22
1
7
Order By: Relevance
“…Using a new chemiluminescence assay and an assay involving the free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) (which are adapted to quantify antioxidants in whole blood), 1 we have shown that erythrocytes, platelets, and lymphocytes not only rapidly scavenge reactive oxygen species but also avidly bind to their surfaces a large variety of antioxidant polyphenols, which further enhance their oxidantscavenging abilities. 2,3 Such complexes could further act synergistically with low-molecular-weight antioxidants in plasma and with albumin to decompose reactive oxygen species.…”
Section: Quantifying Oxidant-scavenging Ability Of Bloodmentioning
confidence: 99%
“…Using a new chemiluminescence assay and an assay involving the free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) (which are adapted to quantify antioxidants in whole blood), 1 we have shown that erythrocytes, platelets, and lymphocytes not only rapidly scavenge reactive oxygen species but also avidly bind to their surfaces a large variety of antioxidant polyphenols, which further enhance their oxidantscavenging abilities. 2,3 Such complexes could further act synergistically with low-molecular-weight antioxidants in plasma and with albumin to decompose reactive oxygen species.…”
Section: Quantifying Oxidant-scavenging Ability Of Bloodmentioning
confidence: 99%
“…Several studies have demonstrated the role of salivary UCL, [30][31][32] although little research has been published that assesses salivary UCL as an index of psychologic stress. We previously reported that the change in salivary UCL before and after an experimental examination might be a new sensitive biomarker of acute psychologic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Zum einen ist es in der Lage, andere, niedermolekulare Antioxidantien zu regenerieren und sozusagen zu «recyceln». Damit könnte es einen wichtigen Beitrag zur Aufrechterhaltung des antioxidativen Netzwerks leisten [18,22]. Zum anderen induzierte der Padma 28-Extrakt den durch Nrf-2 vermittelten ARE(antioxidant response element)-Signalweg [13].…”
Section: Oxidativer Stressunclassified